2016
DOI: 10.1007/s00365-016-9348-0
|View full text |Cite
|
Sign up to set email alerts
|

Conformal Models and Fingerprints of Pseudo-lemniscates

Abstract: Abstract. We prove that every meromorphic function on the closure of an analytic Jordan domain which is sufficiently well-behaved on the boundary is conformally equivalent to a rational map whose degree is smallest possible. We also show that the minimality of the degree fails in general without the boundary assumptions. As an application, we generalize a theorem of Ebenfelt, Khavinson and Shapiro by characterizing fingerprints of polynomial pseudolemniscates.The starting point of this paper is the following c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In 2016, Richards [20] extended this result to general analytic functions which are analytic across the boundary of the unit disk, though this time with no control on the degree of the polynomial. In 2017, T. J. Richards and M. Younsi [23] gave a version of Theorem 4.4 for meromorphic functions, in which they were also able to recover control over the degree of the polynomial p (now a rational function q), subject to a condition on the behavior of the function f on the boundary of the disk. Theorem 4.5.…”
Section: Fingerprints Of Shapes and Conformal Equivalencementioning
confidence: 99%
“…In 2016, Richards [20] extended this result to general analytic functions which are analytic across the boundary of the unit disk, though this time with no control on the degree of the polynomial. In 2017, T. J. Richards and M. Younsi [23] gave a version of Theorem 4.4 for meromorphic functions, in which they were also able to recover control over the degree of the polynomial p (now a rational function q), subject to a condition on the behavior of the function f on the boundary of the disk. Theorem 4.5.…”
Section: Fingerprints Of Shapes and Conformal Equivalencementioning
confidence: 99%
“…Recently Younsi [6] (working jointly with the author) has applied these conformal welding techniques to provide a positive answer to the conformal modeling question for meromorphic functions on psuedo-tracts. That is, it has been shown that if D is a Jordan domain with smooth boundary, and f is meromorphic on cl(D), and f (∂D) is a Jordan curve, then f may be conformally modeled by a rational function r on D. One of the major advantages of this approach is that in the case described above the rational function r may be taken to have the smallest degree possible (namely the maximal number of preimages under f of any point, counted with multiplicity).…”
Section: The Approach Of Younsimentioning
confidence: 99%
“…As far as we know, the most general version is a solution on the online mathematics forum math.stackexchange.com by Lowther and Speyer [4,9] showing that the PCMQ has a positive answer as long as the domain D is bounded and the function f is analytic on the closure of D. This solution relies on approximation by polynomials interpolating certain derivative data, and can readily be generalized to meromorphic functions f , in which case polynomials need to be replaced by rational maps. Also of interest on this topic is the paper of the authors [8] which again brings the tools of conformal welding to bear on the PCMQ, also addressing the question of the degree of the polynomial conformal model in more detail.…”
Section: Introductionmentioning
confidence: 99%